Myelinating Schwann Cell Polarity and Mechanically-Driven Myelin Sheath Elongation - Tricaud, Nicolas (Frontiers in Cellular Neuroscience, 2018)
Myelin sheath geometry, encompassing myelin sheath thickness relative to internodal length, is critical to optimize nerve conduction velocity and these parameters are carefully adjusted by the myelinating cells in mammals. In the central nervous system these adjustments could regulate neuronal activities while in the peripheral nervous system they lead to the optimization and the reliability of the nerve conduction velocity. However the physiological and cellular mechanisms that underlie myelin sheath geometry regulation are not yet fully elucidated. In peripheral nerves the myelinating Schwann cell uses several molecular mechanisms to reach and maintain the correct myelin sheath geometry, such that myelin sheath thickness and internodal length are regulated independently. One of these mechanisms is the epithelial-like cell polarization process that occurs during the early phases of the myelin biogenesis. Epithelial cell polarization factors are known to control cell size and morphology in invertebrates and mammals making these processes critical in the organogenesis. Correlative data indicate that internodal length is regulated by postnatal body growth that elongates peripheral nerves in mammals. In addition, the mechanical stretching of peripheral nerves in adult animals shows that myelin sheath length can be increased by mechanical cues. Recent results describe the important role of YAP/TAZ co-transcription factors during Schwann cell myelination and their functions has been linked to the mechanotransduction through the HIPPO pathway and the epithelial polarity factor Crb3. In this review the molecular mechanisms that govern mechanically-driven myelin sheath elongation and how a Schwann cell can modulate internodal myelin sheath length, independent of internodal thickness, will be discussed regarding these recent data. In addition, the potential relevance of these mechanosensitive mechanisms in peripheral pathologies will be highlighted.